SUNGAI MEANDER LUK ULO ANTARA KONDISI IDEAL DAN KENYATAAN - Nur, Arief Mustofa (Universitas Negeri Semarang, 2014)
Luk Ulo River is the biggest river across Kebumen, Central Java. It crossKarangsambung Area in meander form. Meander River has a sinuosity index >1.5. That’s why, its need to be proven if Luk Ulo River is a meandering river. Thisstudy start with measuring Indonesia’s Map which according to a theory aboutMeander River of Dury (1969) and field study. There are seven segments reveal abend which resemble the letter